PENGEMBANGAN PRODUK EKONOMI HANDCRAFT MELALUI MODEL PROJECT-BASED LEARNING BERBASIS PENDEKATAN STEAM UNTUK MENINGKATKAN KREATIVITAS - Annisa Shaliha; Dini Srikandi Jumarnis Siregar; Rizky Nur Fauziah; Syifa Fatma Khairani; Muhammad Daffa Alaudin; Zaenul Slam (STKIP Subang, 2026)
This study aims to describe students' creativity and teamwork skills in handcraft production activities based on the STEAM approach through the Project Based Learning (PjBL) model. Observations were conducted on 9 female students who were divided into three groups. Each group created products in the form of tulip flower pots made from plastic spoons and beaded bracelets (stringing beads). A descriptive qualitative approach was used, with data collection techniques consisting of structured observations and semi-structured interviews. The results showed that all groups were able to complete their products within the designated time and exhibited a good level of teamwork. However, two out of the three groups still experienced technical difficulties: the first group struggled to tie the ends of the bracelet string, while the third group faced difficulties in joining the sides of the plastic spoons to form the tulip shape. The integration of STEAM elements in the production process, particularly the mathematics aspect (pattern proportion) and the art aspect (color aesthetics), still requires further reinforcement. These findings imply that the consistent implementation of STEAM-based PjBL can be an effective strategy to develop both students' creativity and motor skills.